2003
DOI: 10.1016/s0168-6496(03)00165-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of oligotrophic acido-tolerant methanogenic consortia from a Sphagnum peat bog

Abstract: Two dense and highly enriched (up to 10(9) cells ml(-1), <10% of bacterial satellites) acido-tolerant (pH 4.0-6.5) methanogenic consortia, '26' and 'K', were isolated from the peat beneath a Sphagnum-Eriophorum-Carex community in West Siberia. Both consortia produced methane from CO2:H2 on chemically defined, diluted N-free media containing Ti(III)citrate as reducing agent. The phylogenetic analysis of 16S ribosomal DNA revealed three archaeal and nine bacterial sequence types. Consortium '26' contained single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
95
0
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 55 publications
5
95
0
8
Order By: Relevance
“…It was found that most of the boreal and sub-Arctic wetlands contain a wide diversity of methanogens (40,41) and methanotrophs (42,43), most of them being distantly related to known species. Only recently, some of these obscure microbes were obtained in pure culture or stable consortia (44,45). The novel microbes of methane cycles are extreme oligotrophic species that evolved to function in media with very low concentrations of mineral nutrients.…”
Section: Species Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that most of the boreal and sub-Arctic wetlands contain a wide diversity of methanogens (40,41) and methanotrophs (42,43), most of them being distantly related to known species. Only recently, some of these obscure microbes were obtained in pure culture or stable consortia (44,45). The novel microbes of methane cycles are extreme oligotrophic species that evolved to function in media with very low concentrations of mineral nutrients.…”
Section: Species Diversitymentioning
confidence: 99%
“…The novel microbes of methane cycles are extreme oligotrophic species that evolved to function in media with very low concentrations of mineral nutrients. Taxonomically, the novel oligotrophic methanogens form new species, genera and even families within the Archaea domain (45). The acidophilic methanotrophs form two new groups: Methylocapsa and Methylocella (44,46), the last one affiliating with heterotrophic Beijerinckia indica.…”
Section: Species Diversitymentioning
confidence: 99%
“…DeLong et al, 1994;MacGregor et al, 1997;Schleper et al, 1997;Vetriani et al, 1999;Jurgens et al, 2000;Karner et al, 2001;Keough et al, 2003), peat bogs, wetlands and soils (e.g. Buckley et al, 1998;Ochsenreiter et al, 2003;Sizova et al, 2003;Kotsyurbenko et al, 2004) and the deep subsurface (Takai et al, 2001). Despite being ubiquitous, only a limited number of archaeal cultures is available, mostly thermophiles and methanogens, one 'symbiont culture' of a mesophilic Crenarchaeota: Cenarchaeum symbiosum, an archaeon living in symbiosis with the marine sponge Axinella mexicana (Preston et al, 1996) and a nitrifying crenarchaeote isolated from a sea aquarium (Kö nneke et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous culture-dependent and -independent investigations have provided evidence that members of the RC-I lineage utilize H 2 (Lueders et al, 2001;Sizova et al, 2003;Erkel et al, 2005Erkel et al, , 2006Lehmann-Richter et al, 1999). Erkel et al (2006) constructed a complete genome sequence of an RC-I methanogen from an enrichment culture growing on H 2 and revealed that the RC-I methanogen had a full set of genes involved in methanogenesis from H 2 /CO 2 .…”
mentioning
confidence: 99%
“…Erkel et al (2006) constructed a complete genome sequence of an RC-I methanogen from an enrichment culture growing on H 2 and revealed that the RC-I methanogen had a full set of genes involved in methanogenesis from H 2 /CO 2 . Abundant populations of RC-I Archaea were detected in an acidophilic methanogenic consortium supplemented with H 2 as sole energy source (Sizova et al, 2003). The 16S rRNA gene sequences from those RC-I enrichments were determined and are available from the Genbank/EMBL/ DDBJ databases as AM114193 for the metagenome (the genome contained three rrn operons) and AF524853 for the acidophilic consortium.…”
mentioning
confidence: 99%